Association between body composition and fasting blood glucose in patients with type 2 diabetes - Nazhif Gifari; Rachmanida Nuzrina; Mury Kuswari; Laras Sitoayu (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Type 2 Diabetes Mellitus (T2DM) has become a significant public health issue in Asia, with significantly increasing prevalence rates in recent decades, especially affecting blood glucose levels in patients with this type of diabetes. This study aimed to examine the correlation between body composition and fasting blood glucose levels in subjects with diabetes mellitus type 2. The observational research used a cross-sectional design that included a sample of 68 subjects, conducted between August and May 2024 at the RSUP Fatmawati Hospital in Jakarta. Data were analyzed using the chi-square test for bivariate analysis, and analysis of variance was used to compare the variables. Body composition was measured using body impedance analysis (BIA), physical activity levels were measured using the International Physical Activity Questionnaire Short Form (IPAQ-SF), and fasting blood glucose was measured using Accu-Chek Instant Strips. Dietary and beverage consumption habits, familial health history, smoking habits, sleep duration, and physical activity level were assessed using a structured questionnaire. The results showed a positive relationship between nutritional status, percent body fat, and waist circumference, with a negative correlation between muscle mass and fasting blood sugar levels. In conclusion, nutritional status, percent body fat, waist circumference, and muscle mass were associated with fasting blood glucose levels.